2021
DOI: 10.3390/foods10071648
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Survey in Pecorino Siciliano PDO Cheese

Abstract: The determination of alkaline phosphatase (ALP) in cheeses has become an official method for controlling cheeses with a protected designation of origin (PDO), all of which use raw milk. PDO cheeses, characterized by high craftsmanship, usually have an uneven quality. However, for these cheeses, it is necessary to establish ALP values so that they can be defined as a raw milk product. In this study, a dataset with Pecorino Siciliano PDO samples was analyzed to determine ALP both at the core and under the rind. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Pecorino Siciliano cheese is made using traditional wooden equipment and technology, as reported briefly in Table 1 . The Pecorino Siciliano PDO manufacturing technology is described by Todaro et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pecorino Siciliano cheese is made using traditional wooden equipment and technology, as reported briefly in Table 1 . The Pecorino Siciliano PDO manufacturing technology is described by Todaro et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ALP activity was highest in human colostrum and then decreased with the increase in lactation time [159]. Some studies have found that ALP activity remains in heat-processed cheese [160,161].…”
Section: Alp In Raw Milkmentioning
confidence: 99%
“…The curd is broken to reduce the size of the coagulum to the dimension of rice grains, and syneresis is facilitated by the addition of hot water at a temperature of 70-90 • C. The curd is then placed in moulding rattan baskets where it is pressed firmly to facilitate draining of the whey. The rattan baskets containing the curds are placed in the wooden vat or in a steel tank and coated with hot deproteinized whey (~80 • C) for cooking for approximately 3-4 h [9,10]. The curd is then removed from the rattan baskets, dried at ambient temperature for 24-48 h and salted in saturated brine or by manual dispersion of salt onto the cheese surfaces.…”
Section: Introductionmentioning
confidence: 99%